Kesadaran Ibu Hamil Mendeteksi Dini Kondisi Patologis dan Kegawatdaruratan Selama Kehamilan Sampai Bayi Baru Lahir di Puskesmas Mengwi I Tahun 2018 - Ni Komang Yuni Rahyani; Ni Luh Putu Sri Erawati; Ni Nyoman Suindri; Ni Gusti Ayu Eka Utarini; IGN Sri Partini (Jurnal Pengabmas Masyarakat Sehat, 2019)
The maternal and child health program is an excellent program in the strategy of reducing morbidity and maternal mortality in various countries. Important information given to pregnant women based on the evidence-based in health facilities. The comprehensive information related the efforts to safe the well-being of pregnant women and their babies. The purpose of this community service is to gather information about the difference between knowledge, attitude and skill between pretest and posttest about early detection and management of pathology and emergency condition in pregnant women at Public Health Center I of Mengwi. Method of service using quasi experiment design that is pretest posttest without control approach group design. The number of pregnant women who were involved is 30 people that taken from pregnant women who visited the Public Health Center I of Mengwi for pregnancy examination every Wednesday. Data analysis using anova test. The result of t-test is explained that the level of knowledge, attitude and skill before and after counseling have increased. The value of p = 0,000 means there is a relationship of knowledge, attitude and skills before and after counseling to pregnant women. Pregnant women are expected to seek information related to danger signs and risks during pregnancy until newborn.Keywords: pregnant, skill, referral, pathological, emergency